Gender-Based Violence in Nicole Baart’s Novel “You were Always Mine” - Anggit Hanifah (Morphosis: Journal of Literature, 2024)
This study is aimed to uncover the issue of gender-based violence in a novel that focuses on discovering the depictions of it and the way the protagonist deals with it. The object of this study is a novel entitled You Were Always Mine (2018) by Nicole Baart. The theory of Understanding Gender-Based Violence: National and International Contexts (2015) by Gangoli and Aghtaie is used to analyze the data in this study. This study applies the descriptive qualitative research method. In this study, the writer focuses on women who get exploited by an institution because of their ability to give birth and their social-economic class which makes them easy to be abused by power. The result of gender-based violence in this study shows that it affects the victims’ psychological state. The conclusion shows that the gender-based violence case experienced by the characters is established by patriarchal culture and gender inequality that is also motivated by discrimination against race and lower social class. Keywords: forced adoption, gender-based violence, novel.